2015
DOI: 10.1246/bcsj.20150129
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Photoresponsive Organic–Inorganic Hybrid Magnet: Layered Cobalt Hydroxides Intercalated with Spiropyran Anions

Abstract: To develop an organic–inorganic hybrid photomagnet, we performed the intercalation of sulfonate-substituted spiropyran anions into layered cobalt hydroxides, obtaining the photoresponsive compound, Co(OH)1.84(nSPSO3)0.16·0.8H2O (CoLHSP; nSPSO3: 1′,3′,3′-trimethyl-6-nitrospiro[2H-1-benzopyran-2,2′-indoline]-5′-sulfonate). After UV irradiation (313 nm), the optical and magnetic properties of CoLHSP clearly changed. A new band emerged in the absorption spectrum at 564 nm, corresponding to the π–π* transition in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The frequency dependence in this sort of materials is related to its intrinsically disordered nature and glassy behavior. ,, We have confirmed the spin-glass nature of these compounds by extracting the frequency-shift parameter (also known as the Mydosh parameter ϕ) from the out-of-phase signal We have found ϕ < 0.1 for all the samples, in good agreement with that reported for related hybrid CoAl-LDHs and spin-glass-like materials previously reported. ,,, …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The frequency dependence in this sort of materials is related to its intrinsically disordered nature and glassy behavior. ,, We have confirmed the spin-glass nature of these compounds by extracting the frequency-shift parameter (also known as the Mydosh parameter ϕ) from the out-of-phase signal We have found ϕ < 0.1 for all the samples, in good agreement with that reported for related hybrid CoAl-LDHs and spin-glass-like materials previously reported. ,,, …”
Section: Resultssupporting
confidence: 85%
“…We have found < 0.1 for all the samples, in good agreement with that found for related ϕ hybrid CoAl-LDHs and spin glass-like materials previously reported. 10,43,48,49 expected from a naive point of view, the study revealed that the major factor governing the dipolar interactions between magnetic layers is the spin correlation size, or, in the limit case, the lateral dimension of the layer, rather than the interlayer distance. This explains why the cooperative behavior observed in these materials is largely independent on the interlayer distance and suggests a strong influence of the cation ordering and particle dimensions on the magnetic behaviour.…”
Section: Resultsmentioning
confidence: 83%
“…To develop an organic-inorganic hybrid photomagnet, intercalation of spiropyran-5sulfonate anions into layered cobalt hydroxides was performed, yielding SP159-CoLHSP photoresponsive compound [62,63]. Target spiropyran-5 -sulfonate was synthesized from K salt SP160, which was prepared by condensation of Fischer's base analog (2-methylene-1,3,3-trimethylindoline-5-sulfonato potassium salt) with salicylaldehyde derivatives at reflux.…”
Section: Synthesis Of the 5 -Substituted Spiropyran Derivatives Side ...mentioning
confidence: 99%
“…The gigantic anisotropy of the lattice, coupled with the tunable spin state of Co cations, renders these compounds with intriguing physical and chemical properties. [16][17][18][19][20][21] Compounds of layered cobalt hydroxide can be divided into two categories: the βand the α-phase. The β-phase, e.g., Co(OH) 2 , consists of brucite-like neutral host layers built by edge-sharing [Co(OH) 6 ] octahedra (Co Oh ).…”
Section: Introductionmentioning
confidence: 99%